Commentary: Energy Deregulation in Maine - Flannigan, David; Weil, Gordon; Diamond, Stephen; Ward, Stephen; Gordon, Kenneth; Connors, Jim (Maine Policy Review, 2001)
Recent stories from California of power blackouts, utility bankruptcies, and skyrocketing rates have left many wondering whether Maine is going to suffer a similar fate. Like California, Maine has deregulated its electricity supply—an idea that sounded good to many, but which now has some questioning whether consumers will be made better off or worse. To address these issues, MPR asked six analysts to comment on electricity deregulation in Maine. Some address whether Maine is destined to follow in California’s footsteps. Others question whether regional decision making entities, such as the New England Power Pool and the Independent System Operator of New England, sufficiently represent the public interest. Still others address whether there is a future role for public conservation programs. Together, they suggest Maine will not befall the fate of California, but they also suggest that electricity deregulation in Maine may bring its own troubles if we’re not attentive and forward-thinking today.